Pengaruh Edutainment Ular Tangga Terhadap Perilaku Remaja Tentang Personal Hygiene Menstruasi - Zuhriya, Cholilatul; Armini, Ni Ketut Alit; Wahyuni, Erna Dwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Background: Teenagers have problems related to personal hygiene during menstrual periods due to lack of explanation and health services. Lesser sources of information lead to lower knowledge and will impact on the attitudes and actions of teenagers. Edutainment of ladders snakes can be applied as a solution to this problem. Objective: The purpose of this study was to explain the effect of ladders snakes edutainment to teenagers behavior about personal hygiene menstruation. Methods: Quasy experiment was used to design this study with the sample consist of 33 respondents for each treatment and control group. Data were obtained from questionnaire to measure teenagers’ knowledge, attitude, and action about personal hygiene menstruation. Analysis data of this study was using nonparametric method based on Wilcoxonn Signed Rank tests and Mann Whitney U-Test with significance value α ≤ 0,05. Results: The results of the study showed an increase in knowledge (p = 0,000), attitudes (p = 0,000), and action (p = 0,000) after intervention of the treatment group. This data is also reinforced by statistical analysis Mann Whitney U-Test shows significant differences for knowledge (p = 0,000), attitude (p = 0,000), and action (p = 0,000). Conclusion: The conclusion is edutainment of ladder snakes has an effect on improving teenagers behavior about personal hygiene of menstruation. As an educator, nurse could be use edutainment of ladder snakes for alternative for gives entertain health education on school.